Executive Committee Minutes 2010-05-06 - Academic Senate:::::::::
Emeritus Faculty Position on the Senate, BS changes in Geology, Name change of LSEE to LEEE, Linguistics minor move from Anthropology to English, 3-Unit GE Policy, Information from EPC: waitlist, education autism, curriculum guide, Faculty Listserv